METODE PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) PADA PEMBELAJARAN BAHASA INGGRIS SD KELAS 5 MENGGUNAKAN TRAVELOPOLY SEBAGAI UPAYA PENINGKATAN KOMUNIKASI SISWA - Triana Sari, Ely; Yuniwati, Ika; Yustita, Aprilia Divi (Jurnal Abdimas Bina Bangsa, 2024)
Efforts to improve communication skills are carried out through improving literacy skills in formal education. Both through elementary school to junior high school. Communication skills will improve if literacy skills increase. A number of students from SDN 1 Watukebo revealed that language learning can be more fun by using games. This community service process is carried out to improve student communication with fun learning using the Monopoly Game called TRAVELOPOLY (Tourist Routes and Visits Engage Language Learning Monopoly Game). The service method used is the PAR (Participatory Action Research) method where the implementer and the teacher both conduct learning using the TGT Method. The results of this service include the development of the TRAVELOPOLY Game; increase students' pretest and posttest scores; and improving the communication skills of students. The improvement in English communication of class 5A students was 10 students, while class 5B as many as 16 students